The Effect of Price Perception, Product Reviews, and Product Appearance on Purchasing Decisions - Rijal, Khusnur; Sukresna, I Made (LifeSciFi, 2024)
In 2023 Shopee will be the marketplace with the most visitors in Indonesia (January-December 2023). In that period Shopee recorded around 2.3 billion visits, far surpassing its competitors. Shopee not only wants to create a better life through technology, but also has a mission to address environmental issues and support environmental sustainability. This research aims to determine price perceptions, product reviews and product appearance on purchasing decisions through trust as an intervening variable, with a focus on Shopee consumers in Pekalongan City. The sampling technique used non-probability sampling technique with 120 respondents who met the criteria. The data analysis technique in this research is Structural Equation Modelling (SEM) which is measured through AMOS (Analysis of Moment Structure) tools or applications. The results of this research show that price perceptions, product reviews, and product appearance significantly influence purchasing decisions through trust as an intervening variable for Shopee consumers in Pekalongan City. These findings emphasize the importance of increasing perceived price appropriateness, obtaining good product reviews, and presenting consumers with an attractive product appearance to strengthen trust and influence purchasing decisions.